High prevalence of Mucosa-Associated extended-spectrum β-Lactamase-producing Escherichia coli and Klebsiella pneumoniae among Iranain patients with inflammatory bowel disease (IBD) - Ayda Afshari Kharaghani; Naser Harzandi; Babak Khorsand; Mohsen Rajabnia; Azin Afshari Kharaghani; Hamidreza Houri (BMC, 2023)
Abstract Background Several pieces of evidence suggest that certain pathobionts belonging to Enterobacterales are associated with the development and progression of inflammatory bowel diseases (IBD). Extended-spectrum β-lactamases (ESBLs) ESBLs are frequently found in the Enterobacterales members, particularly in Escherichia coli and Klebsiella spp., and might trigger antibiotic-induced perturbations of the intestinal microbiota and led to more severe disease activity in IBD. Therefore, the severity of IBD could be influenced by ESBL-producing Enterobacterales, and hence, this study aimed to investigate the presence of ESBLs and carbapenemases among mucosa-associated E. coli and Klebsiella pneumoniae isolated from colonic biopsies of Iranian patients with IBD. Methods In this cross-sectional study, E. coli and K. pneumoniae were isolated from inflamed ileum and/or colon tissue of patients with IBD, including Ulcerative colitis (UC) and Crohn's disease (CD), during colonoscopy. Demographic data and clinical characteristics were recorded, and UC and CD disease activity and extent were evaluated according to the full Mayo score and Crohn's disease activity index (CDAI), respectively. Phenotypic and molecular detection of ESBL- and carbapenemase-producing E. coli and Klebsiella pneumoniae were carried out. Disease activity and other clinical and microbial features were compared in patients with and without gut colonization with ESBL producers. Results A total of 83 IBD patients, including 67 UC and 16 CD, were enrolled in the initial analysis. Intestinal colonization with ESBL-producing E. coli and/or Klebsiella pneumoniae was found in 37 (55.2%) of UC and 9 (56.2%) of DC patients - mostly harbored E. coli containing the bla CTX−M and bla TEM genes. UC patients with intestinal colonization with ESBL-producers had more severe disease compared with patients without colonization. Moreover, 10.2% of tested E. coli and 34.8% of K. pneumoniea were recognized as potential carbapenemase producers. Conclusion Intestinal colonization with ESBL producers could arise disease activity in IBD patients. Further large-scale case-control studies should be performed to investigate the possible confounding factors that could contribute to this outcome.